2021
DOI: 10.1080/21678421.2021.1946084
|View full text |Cite
|
Sign up to set email alerts
|

ALS patients with concurrent neuroinflammatory disorders; a nationwide clinical records study

Abstract: Objective:To determine if inflammation in proximity of the motor unit may contribute to neurodegeneration in amyotrophic lateral sclerosis (ALS). Methods: We identified all patients diagnosed in Sweden with concurrent ALS and multiple sclerosis (MS), myasthenia gravis (MG), inflammatory polyneuropathies (IP), or dermatopolymyositis (DMPM) during 1991-2014 according to the Swedish Patient Register (N ¼ 263). We validated medical records for 92% of these patients (18 records were not retrieved and three did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Indeed, concurrent MG may occur in a small proportion of patients with onset of motorneuron disease. 26…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, concurrent MG may occur in a small proportion of patients with onset of motorneuron disease. 26…”
Section: Discussionmentioning
confidence: 99%
“…However, large epidemiological studies suggested an association between MS and ALS [ 25 , 26 ], with an increased risk of MS among children of ALS patients [ 27 , 28 ]. If co-occurrence of ALS and MS is often due to diagnostic uncertainty [ 29 ], in validated cases of co-occurrence, the MS-related neuroinflammatory symptoms occurred years before ALS onset, leading to hypothesize that, in a small subgroup of ALS patients with defined clinical characteristics, neurodegeneration may be triggered by preceding neuroinflammation around the motor unit [ 29 ]. Thus, it could be possible that the inflammatory pathways activated by mitochondrial dysfunctions can contribute to neuroinflammation observed in MS, and in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…As previous reviews have summarized the existing literature on the roles of specific diseases, including cardiometabolic and inflammatory diseases, on the risk of ALS [60,61], in the present review, we focused on medication use as potential risk factor for ALS. However, because among the studies included in the present review, few have made efforts to address the concern of indication bias, it remains largely unknown whether it is the use of a specific medication or its underlying disease that is the real relevant factor for ALS.…”
Section: Discussionmentioning
confidence: 99%